2014
DOI: 10.1073/pnas.1406926111
|View full text |Cite
|
Sign up to set email alerts
|

Charge transport and rectification in molecular junctions formed with carbon-based electrodes

Abstract: Molecular junctions formed using the scanning-tunneling-microscope-based break-junction technique (STM-BJ) have provided unique insight into charge transport at the nanoscale. In most prior work, the same metal, typically Au, Pt, or Ag, is used for both tip and substrate. For such noble metal electrodes, the density of electronic states is approximately constant within a narrow energy window relevant to charge transport. Here, we form molecular junctions using the STM-BJ technique, with an Au metal tip and a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
100
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(109 citation statements)
references
References 38 publications
8
100
1
Order By: Relevance
“…For comparison, Venkataraman et al found that the tunneling decay is 1.71 per phenyl group with Au-amine contact [5], while Wold et al reported 1.76 per phenyl group with Au-thiol contact by using conducting probe atomic force microscopy [31]. More recently, tunneling decay constant of 1.74 per phenyl group for Ag junctions was observed for oligophenyls with amine group [32]. Our results are thus in line with the literature.…”
Section: Influence Of Molecular Length On Single-molecule Conductancesupporting
confidence: 92%
“…For comparison, Venkataraman et al found that the tunneling decay is 1.71 per phenyl group with Au-amine contact [5], while Wold et al reported 1.76 per phenyl group with Au-thiol contact by using conducting probe atomic force microscopy [31]. More recently, tunneling decay constant of 1.74 per phenyl group for Ag junctions was observed for oligophenyls with amine group [32]. Our results are thus in line with the literature.…”
Section: Influence Of Molecular Length On Single-molecule Conductancesupporting
confidence: 92%
“…Furthermore, given that the tip and substrate materials do not make physical contact, the method is ideal for studies of surface-orientated asymmetrical molecules (probing single-molecule rectification 36−38 ), on-surface (in situ) synthesized/modified components, 39,40 or experiments involving heterogeneous electrodes. 41, 42 In a first step toward pursuits along these lines, herein we report an automated I(s) data collection methodology (capable of recording 10 000 I(s) measurements in ∼8 h) and a novel, mathematically rigorous data sorting algorithm which makes no assumptions about plateau shape (processing 10 000 I(s) measurements in ∼2 h). With our approach, the number of measurements per experiment can be increased by 2 orders of magnitude compared to previous studies 5,13,15,[19][20][21]24 using this method.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A single-molecule diode, a circuit element that directs current flow 4 , was first proposed more than 40 years ago 5 and consisted of an asymmetric molecule comprising a donor-bridge-acceptor architecture to mimic a semiconductor p-n junction. Several singlemolecule diodes have since been realized in junctions featuring asymmetric molecular backbones [6][7][8] , molecule-electrode linkers 9 or electrode materials 10 . Despite these advances, molecular diodes have had limited potential for applications due to their low conductance, low rectification ratios, extreme sensitivity to the junction structure and high operating voltages [7][8][9]11,12 .…”
mentioning
confidence: 99%